2018
DOI: 10.1021/acs.jpcc.8b05992
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Analysis of Excitation Dynamics in Dye-Sensitized Upconversion Core and Core/Active Shell Nanoparticles

Abstract: Upconversion nanoparticles (UCNPs) combining both dye sensitization and core/shell enhancement are of great interest for their ability to boost the excitation efficiency of upconversion systems. Here, we report and investigate a 20-fold upconversion luminescence enhancement in dye-sensitized core/active shell UCNPs compared to that in nonsensitized core-only UCNPs. We observe a two-component luminescence rise dynamics in the upconversion kinetics of dye-sensitized UCNPs, distinctly different from the one-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…70 It is also possible to dope the shell with Yb 3+ ions instead of typically used Nd 3+ ions, as was done for IR-806 sensitized NaYF 4 :Yb 3+ ,Er 3+ /NaYF4:Yb 3+ and IR-820 bound NaLuF 4 : Gd,Yb,Er/NaLuF 4 :Yb,Pr core/shell NPs. [71][72][73] These single sensitizerdoped NPs utilize a single exclusive energy transfer pathway for the transfer of absorbed energy from the dye molecules, across the inorganic shell and subsequently to the ions in the core. An availability of multiple energy transfer pathways across the shell holds a possibility to boost the UC efficiency.…”
Section: Core/shell Nanoparticlesmentioning
confidence: 99%
“…70 It is also possible to dope the shell with Yb 3+ ions instead of typically used Nd 3+ ions, as was done for IR-806 sensitized NaYF 4 :Yb 3+ ,Er 3+ /NaYF4:Yb 3+ and IR-820 bound NaLuF 4 : Gd,Yb,Er/NaLuF 4 :Yb,Pr core/shell NPs. [71][72][73] These single sensitizerdoped NPs utilize a single exclusive energy transfer pathway for the transfer of absorbed energy from the dye molecules, across the inorganic shell and subsequently to the ions in the core. An availability of multiple energy transfer pathways across the shell holds a possibility to boost the UC efficiency.…”
Section: Core/shell Nanoparticlesmentioning
confidence: 99%
“…In order to increase the effectiveness of UC, studies on the specific energy-transfer method of dye sensitization of UCNPs have been conducted recently. From analysis of the UC kinetics between the dyes and UCNPs (NaYF 4 :20%Yb 3+ ,2%Er 3+ @NaYF 4 :10%Yb 3+ ), it was found that the UC kinetics of UCNPs without dye sensitizing had one-component rise dynamics, and a two-component UCL kinetics in the rise dynamics of dye-sensitized UCNPs (Figure a) . Fluorescence attenuation measurements showed that energy transfer between the dye and Er 3+ is more efficient than that between Yb 3+ and Er 3+ .…”
Section: Common Commercial Dye-sensitized Ucnpsmentioning
confidence: 99%
“…Additionally, the image includes fluorescence decay curves of the IR-806 dye-sensitized core (black) and the molecules bound to the core-only UCNPs (red curve). Reprinted with permission from ref . Copyright 2018 American Chemical Society.…”
Section: Common Commercial Dye-sensitized Ucnpsmentioning
confidence: 99%
“…Recent developments regarding the synthesis of nanomaterials have made possible the fabrication of a range of nanoparticles with rich chemical compositions and a variety of morphologies, which enable the tuning of their optoelectronic properties. [1][2][3] Further tailoring in properties is achieved by modifying the surface ligands of the nanoparticles, which enrich them with additional functions such as the ability to self-assemble to mesoscale structures, deliver cargo of interest (e.g., drugs), selectively bind molecules (e.g., mRNA) and disperse in complex media whilst maintaining their stability. [4][5][6][7][8][9][10][11][12][13][14][15] The design of biosensors, which incorporate the use of nanomaterials is of particular interest as it enables the early diagnosis of diseases, which has proven to be vital for patient treatment and survival.…”
Section: Introductionmentioning
confidence: 99%